THEORETICAL INTERPRETATIONS OF SOCIAL INEQUALITIES IN EDUCATION - Marinković, Blagica (National interest, 2024)
Exploring the complexities of social inequalities in education involves delving into various theoretical perspectives that offer nuanced insights into the origins, mechanisms, and consequences of educational disparities. Functionalist theories, as advocated by eminent sociologists like Émile Durkheim, Talcott Parsons, and Robert Merton, perceive education as a crucial institution for fostering social cohesion and transmitting societal norms and values. According to this perspective, education plays a pivotal role in moulding individuals to assume specific roles within society, thereby reinforcing social unity and cultural continuity. It is seen as a mechanism through which shared values and knowledge are imparted, contributing to the stability and functioning of society as a whole. In contrast, radical theories, as articulated by scholars such as Louis Althusser, Samuel Bowles, and Herbert Gintis, offer a critical examination of education as a tool for perpetuating existing social hierarchies. They argue that the educational system serves to maintain the dominance of the ruling class while simultaneously suppressing the aspirations of marginalized groups. From this viewpoint, education is viewed as a mechanism of social control, perpetuating inequality by limiting the upward mobility of individuals, particularly those from disadvantaged backgrounds. The emphasis is placed on how the structure of education reinforces and reproduces existing power dynamics within society.The conceptual framework of educational capital, prominently developed by Pierre Bourdieu and Jean-Claude Passeron, provides a comprehensive lens through which to analyse social stratification within educational systems. Their work emphasizes that economic factors alone cannot fully account for the reproduction of social inequalities in education. Instead, they highlight the crucial roles played by cultural capital, social capital, and symbolic capital in shaping educational outcomes.Bourdieu's theory of cultural capital underscores the significance of non-economic resources such as knowledge, skills, and language proficiency in determining educational success. He argues that unequal access to cultural capital perpetuates advantages for privileged social groups, contributing to the reproduction of social inequalities across generations. Building upon Bourdieu's insights, Passeron introduces the concepts of social capital and symbolic capital. Social capital refers to the networks and relationships individuals possess, which can influence their educational opportunities and trajectories. Symbolic capital, on the other hand, pertains to the prestige and symbolic value associated with educational credentials, which can confer advantages or disadvantages in social interactions and life opportunities.In summary, these theoretical perspectives offer diverse lenses through which to understand the multifaceted nature of social inequalities in education. While functionalist theories underscore education's role in maintaining social order and stability, radical theories unveil its function in perpetuating societal divisions and reinforcing existing power structures. The educational capital framework provides a nuanced picture of how different types of capital interact to shape educational opportunities and outcomes, highlighting the complex interplay between individual agency, social structures, and cultural contexts in determining educational trajectories.In this paper, social inequalities in education are analysed through different theoretical explanations of this problem. Differences in educational success among social groups were investigated, with a focus on the influence of social background. Emphasis is placed on the influence of social origin on the educational achievements and educational aspirations of students, and in that context the most relevant theoretical understandings are indicated.
Keywords: Theoretical interpretations; social inequalities; factors; educational process